Roof & restitutie de uittocht en gedeeltelijke terugkeer van Nederlands kunstbezit tijdens en na de Tweede Wereldoorlog - Ekkart, Rudolf E. O. 1947- (Ter Borch Stichting, 2017)
'Looted Art' is the story of Jewish art dealers and private collectors whose artworks fell into German hands during the Second World War. This was often a matter of forced sales, and sometimes of organized looting. The works on display are on loan from the Dutch state collection and Dutch museums. In addition, there are some families that have loaned their successfully reclaimed artworks for this remarkable exhibition. Tickets can be obtained at the Bergkerk exhibition space, at the tourist office and on this website.